Minimal B Cell Extrinsic IgG Glycan Modifications of Pro- and Anti-Inflammatory IgG Preparations in vivo - Schaffert, Anja; Hanić, Maja; Novokmet, Mislav; Zaytseva, Olga; Krištić, Jasminka; Lux, Anja; Nitschke, Lars; Peipp, Matthias; Pezer, Marija; Hennig, René; Rapp, Erdmann; Lauc, Gordan; et al. (Frontiers in Immunology, 2020)
Select residues in the biantennary sugar moiety attached to the fragment crystallizable of immunoglobulin G (IgG) antibodies can modulate IgG effector functions. Thus, afucosylated IgG glycovariants have enhanced cytotoxic activity, whereas IgG glycovariants rich in terminal sialic acid residues can trigger anti-inflammatory effects. More recent evidence suggests that terminal α2,6 linked sialic acids can be attached to antibodies post IgG secretion. These findings raise concerns for the use of therapeutic antibodies as they may change their glycosylation status in the patient and hence affect their activity. To investigate to what extent B cell extrinsic sialylation processes modify therapeutic IgG preparations in vivo, we analyzed changes in human intravenous IgG (IVIg) sialylation upon injection in mice deficient in B cells or in mice lacking the sialyltransferase 1, which catalyzes the addition of α2,6 linked sialic acid residues. By performing a time course of IgG glycan analysis with HILIC-UPLC-FLR (plus MS) and xCGE-LIF our study suggests that therapeutic IgG glycosylation is stable upon injection in vivo. Only a very small fraction of IgG molecules acquired sialic acid structures predominantly in the Fab - but not the Fc portion upon injection in vivo, suggesting that therapeutic antibody glycosylation will remain stable upon injection in vivo.